Regional Statistical Models for the Estimation of Flood Peak Values at Ungauged Catchments: Peninsular Malaysia - Al-Mamun, Abdullah; Hashim, Alias; Amir, Zalin (American Society of Civil Engineers, 2012)
Multivariate regional statistical models were developed to estimate flood peak values of various return periods in the Peninsular Malaysia. Annual maximum flood peak data was collected, screened and analysed to identify the river gauging stations potential to produce identical flood frequency curves. The Peninsula was divided into ten (10) flood regions. The mean annual flood (MAF) for each region was considered as the function of catchment area (A) and mean annual rainfall (MAR). The regional equations exhibited good coefficient of determination (R2). Except for the west of Johor Baru State (Region F6) which showed R2 value of 0.874, other regions had values higher than 0.90. The regions located along the east coast of the Peninsula exhibited better coefficients of determination compared to those for the west coast, due to the influence of the north‐east monsoon along the east coast. Mean index errors (MIE) with respect to the actual MAF of each flood region are provided for the users to rationalise the design flood peak values to minimise the uncertainty in the predictions. Flood frequency values for the lower, mean and upper limits were proposed to reduce the effect of outliers and uncertainty in prediction of flood peak values. Knowing the catchment area and MAR of the regions, the design flood peaks of various frequencies can be estimated by the users for the rural ungauged catchments in the Peninsula.